Valuing natural capital amidst rapid urbanization: assessing the gross ecosystem product (GEP) of China’s ‘Chang-Zhu-Tan’ megacity - Ziying Zou; Tong Wu; Yi Xiao; Changsu Song; Kelin Wang; Zhiyun Ouyang (Environmental Research Letters, 2020)
Gross Ecosystem Product (GEP) is an aggregate measure of the monetary value of final ecosystem services, or the direct benefits that people derive from nature. In this study, we focus on the ‘Chang-Zhu-Tan’ (CZT) urban agglomeration—an emerging megacity of over 15 million people situated on the Yangtze River—as a case study of the dynamics of ecological production amidst rapid urbanization. In this study, we couple a spatial-temporal analysis of regional ecological change based on remote-sensing data with economic valuation methods (e.g. travel cost method) using official statistics and survey data. We find that while the land cover of natural ecosystems decreased slightly between 2000 and 2015, their quality—and therefore economic value—greatly improved. From 2000 to 2015, the GEP of CZT increased by 56.77%. In particular, the value of regulating services grew by 7.43% (calculated using inflation-adjusted prices). GEP can reflect nature’s contribution to human well-being. At the same time, its long-term trends can serve as an indicator of the extent and quality of local and regional ecosystems, thereby providing a corrective or complement to more conventional measures of development. Although urbanization increases spatial constraints on the management of natural capital, progress in ecological protection and restoration can still improve the quality of ecosystems and the services they provide. Our study shows how GEP, and the value of natural capital it reflects, can grow amidst the pressures of rapid urbanization.